Comparing SAR based short time-lag cross-correlation and Doppler derived sea ice drift velocities - Kræmer, Thomas; Johnsen, Harald; Brekke, Camilla; Engen, Geir (IEEE Transactions on Geoscience and Remote Sensing, 2017)
Accepted manuscript version. Published version available in IEEE Transactions on Geoscience and Remote Sensing 2018, 56(4). This paper shows initial results from estimating Doppler radial surface velocities (RVLs) over Arctic sea ice using the Sentinel-1A (S1A) satellite. Our study presents the first quantitative comparison between ice drift derived from the Doppler shifts and drift derived using time-series methods over comparable time scales. We compare the Doppler-derived ice velocities with global positioning system tracks from a drifting ice station as well as vector fields derived using traditional cross correlation between a pair of S1A and Radarsat-2 images with a time lag of only 25 min. A strategy is provided for precise calibration of the Doppler values in the context of the S1A level-2 ocean RVL product. When comparing the two methods, root-mean-squared errors (RMSEs) of 7 cm/s were found for the extra wide (EW4) and EW5 swaths, while the highest RMSE of 32 cm/s was obtained for the EW1 swath. Though the agreement is not perfect, our experiment demonstrates that the Doppler technique is capable of measuring a signal from the ice if the ice is fast moving. However, for typical ice speeds, the uncertainties quickly grow beyond the speeds we are trying to measure. Finally, we show how the application of an antenna pattern correction reduces a bias in the estimated Doppler offsets.